Identification of land payments risk zones in establishing territorial community boundaries using GIS - Ibatullin, Sh.; Sakal, O.; Voitiuk, A.; Derkulskyi, R.; Bratinova, M. (Land Management, Cadastre and Land Monitoring, 2024)
Abstract. The article is dedicated to the concept of "tax risk zones," their identification using Geographic Information Systems (GIS), and the role of these zones in the process of establishing territorial community boundaries. The authors examine the impact of the administrative-territorial reform carried out in Ukraine on the spatial identification of land parcels as tax objects. One of the main issues arising during the process of establishing territorial community boundaries is the emergence of tax uncertainty zones and the potential for land disputes between neighboring communities. In such zones, territorial communities risk losing land tax revenue due to uncertainty about the ownership of land parcels by one community or another. The article emphasizes the need for accurate data on land parcels to effectively shape tax policies at the local level. The use of GIS allows the identification of these tax risk zones and provides tools for decision-making regarding the optimization of community boundaries. The article provides examples of the application of GIS for the analysis of spatial data on territorial boundaries and land parcels, as well as an assessment of potential local budget losses due to uncollected land tax and rental payments.Keywords: Tax map of Ukraine, land tax, rental payment, compliance risk, CATUTTC, land management, COATSU, land management documentation.
Keywords: tax map of Ukraine; land tax; rental payment; compliance risk; CATUTTC; land management; COATSU; land management documentation